Association of Serum Leptin and C-Reactive Protein in Women with Breast Cancer - Zainab M Al-Shammaa; Faris A Ahmed (College of Pharmacy / Mustansiriyah University, 2018)
This study was conducted to evaluate the association of serum leptin and hs C-reactive protein with breast cancer. Two groups were included in the study. The first group included 45 newly diagnosed women with breast cancer. The second group included 42 women with benign breast lump as a control group. Blood samples (5 mL) were taken from the patient and the control groups and analyzed for serum leptin and hs C-reactive protein. Serum CA15-3 was also measured in breast cancer patients. The epidermal growth factor receptor 2 (HER2/neu), estrogen and progesterone receptors were determined in breast cancer patients by using immune-chemical method. Serum leptin was significantly higher (p ≤ 0.05) in breast cancer patients than that in the control group; however, no significant difference was noticed between the two groups for serum hs C-reactive protein. No significant difference was noticed between HER2/neu positive or negative in breast cancer patients for serum leptin or hs C-reactive protein. However, serum CA15-3 in HER2/neu positive patients was significantly higher (p ≤ 0.05) than that in HER2/neu negative patients. No significant difference was noticed between positive and negative estrogen breast cancer patients for serum leptin, hs C-reactive protein or CA15-3. In addition, no significant difference was noticed between positive and negative progesterone for serum leptin, hs C-reactive protein or CA15-3. A strong significant positive correlation was noticed between serum leptin and BMI in the control group; however, no significant correlation was noticed between serum leptin and BMI in the breast cancer patients. In conclusion, serum leptin may be used as a prognostic factor for breast cancer. Serum C-reactive protein in HER2/neu positive breast cancer patients is higher than in HER2/neu negative patients.